Power Sharing, Tracing And Prediction Of Losses For Deregulated Operation Of Power Systems - Nallagownden, Perumal (2011)

(untitled)
Fully deregulated energy market consists of a number of generation providers, a number of transmission system operators, and a number of retailers. The capability to predict the contribution of each generator to a retailer’s demand, the power loss in the transaction, the line losses associated with the transaction are necessary to frame transaction and transmission service hiring contracts. A comparative study of the different loss allocation methods namely Pro rata, Incremental allocation and Proportional sharing was carried out on the 14-bus, 24-bus IEEE RTS system, and from the results it was concluded that the proportional sharing method is the most suitable method to be used in this research.